2006
DOI: 10.1007/s10459-006-9036-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Metacognitive Intervention on Students’ Approaches to Learning and Self-Efficacy in a First Year Medical Course

Abstract: Over the course of first-year medical studies, students lose self-efficacy and move away from deep-strategic learning approaches towards more surface approaches. The program of metacognitive activities failed to reverse this trend. The substantial swing towards surface learning raises questions about the perceived capacity of PBL curricula to promote deep approaches to learning in dense curricula, and reinforces the importance of personal and contextual factors, such as study habits, workload and assessment, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 49 publications
8
87
0
5
Order By: Relevance
“…Contextual factors which are considered important include previous educational experiences, particularly the learning environments, characteristics of the academic discipline and the manner in which teaching, learning and assessment are conducted (Vermunt 2005). This approach, offering a much broader perspective on other factors that influence student learning, is supported by the findings of a recent study in which first-year medical students reverted from a deep learning approach to a superficial approach despite a programme of metacognitive activities designed to facilitate deep learning (Papinczak et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Contextual factors which are considered important include previous educational experiences, particularly the learning environments, characteristics of the academic discipline and the manner in which teaching, learning and assessment are conducted (Vermunt 2005). This approach, offering a much broader perspective on other factors that influence student learning, is supported by the findings of a recent study in which first-year medical students reverted from a deep learning approach to a superficial approach despite a programme of metacognitive activities designed to facilitate deep learning (Papinczak et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, looking at individual studies effect sizes, it was striking to see that they ranged from −0.53 to 0.93 for the deep approach, and from −0.50 to 0.50 for the surface approach. The density of the curriculum, unclear goals, perception of cognitive load, insufficiently aligned assessment and workload were some of the factors that have been shown to counter-influence the desired outcome of PBL and other constructivist learning environments on stimulation of deep approach [12,44,4749]. In this line, a previous study suggested that the practice of PBL may evolve along a PBL-based curriculum and move away from the original model [50].…”
Section: Discussionmentioning
confidence: 99%
“…dimiento académico y que se relaciona con el enfoque profundo de aprendizaje (25,26) . Por otra parte, existen resultados contradictorios en relación a la edad y los enfoques de aprendizaje (26,27) .…”
Section: Discussionunclassified